Emergency service management of bodypacking cases caught on the highway outside the borderline (Annals of Medical Research, 2024)
While drug trafficking is a major problem worldwide, body packing involving the storage of narcotic drugs in the human body represents an emergency because of the risk of deadly narcotic toxicity, intestinal obstruction and visceral perforation. We presented the evaluation of body packer cases, which have not been seen before in this region, in the emergency clinic. This study analyzes the medical records of body packers from January to July 2023. Hematological and biochemical tests, abdominal radiographs and tomographies, and removed packages were evaluated in all cases. Nine body packer cases carrying narcotic substances were observed in this study. The mean age was 33 ± 6.3, 2 (22%) were female and 7 (78%) were male. None of the patients required emergency surgery. One patient had acute narcotic intoxication. In this patient, whose packages were observed to be intact, drug intoxication was associated with substance use. Abdominal radiography diagnosed all cases and all were recovered and discharged. It is very important for public safety to diagnose body packing cases and prevent the transport of packages. In this issue, emergency physicians should have radiography and CT imaging features in asymptomatic body packing cases.
Keywords: Bodypacking; Emergency service; Narcotic drugs